Effects of IoT–PLC-Based Smart-Industry Learning Model on Problem-Solving and Critical Thinking Skills of Electrical Engineering Students - Chusna, Chufadatul; Purnomo; Sutadji, Eddy (LP3kM Buddhi Dharma University, 2026)
This study examines the effect of an IoT–PLC-based Smart-Industry learning model on students’ problem-solving and critical thinking skills in electrical engineering education. However, empirical studies investigating how IoT–PLC-based instructional models influence higher-order cognitive skills remain limited, particularly in vocational and electrical engineering education contexts. Despite the increasing integration of Industry 4.0 technologies in education, previous studies have primarily focused on technical skill development and often lack empirically validated pedagogical frameworks. The study employed a quantitative quasi-experimental design with a pretest–posttest control group, involving an experimental group taught through the IoT–PLC-based Smart-Industry learning model and a control group taught through conventional instruction. A total of 60 undergraduate students were selected through cluster sampling and assigned to experimental and control groups. Data were collected using validated instruments, with reliability confirmed by Cronbach’s alpha coefficients above 0.70. The results indicate that the experimental group achieved significantly higher improvements than the control group (p < 0.05), with large effect sizes observed for both problem-solving (d = 1.45) and critical thinking (d = 1.39). These findings suggest that an IoT–PLC-based Smart-Industry learning model may enhance higher-order cognitive skills, particularly problem-solving and critical thinking, within the specific context of electrical engineering education.